Final appraisal report on BRAC's rural development programme (1990-1992) and the BRAC Bank project - BRAC (© BRAC, 2016)
1. Introduction 2. BRAC in perspective 3. Social change and institutional development 4. RDP (Rural Development Programme) 5. BRAC Bank 6. Other programmes 7. Management 8. BRAC's environment 9. Funding and donor requirments.